(untitled) (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
Formulation of the problem. To achieve a neutral level of soil degradation, it is necessary to apply agrotechnologies that ensure the restoration of soil fertility and prevent environmental pollution. At the same time, it is important to establish rational parameters of the nutrient balance, taking into account soil properties and prospects for their improvement. The purpose of the research – to determine the effect of fertilizer application systems in a field crop rotation on the removal of main nutrients with the main products, as well as their balance and its intensity in podzolized chernozem of the Right-Bank Forest Steppe. Research methods. The study was conducted in a long-term (since 2010) stationary field experiment of the Uman National University. The balance of the main nutrients in the soil was calculated using a simplified scheme. The input part of the balance included only the supply of nutrients by mineral fertilizers, and for nitrogen, also symbiotic fixation by soybeans. Since the efficiency of nitrogen fixation was not studied in the experiment, the nitrogen fixation coefficient was assumed to be 60 %. In the output part, the removal of nutrients from the main products was taken into account. Research results. The average annual increase in the yield of the main products of crop rotation crops, depending on the fertilization system, compared to the absolute control (5.04 t/ha of grain units), increased by 1.57–3.58 t/ha of grain units, or by 31–71 %. Exclusion of the nitrogen component from the complete mineral fertilizer (N110P60K80 per 1 ha of crop rotation area) reduced crop rotation productivity by 36%, phosphorus by 17 %, and potassium by 12 %. The smallest decrease (4–6 %) was observed in the experimental variants N110P60K40 and N110P30K80. The average annual removal of nitrogen, P₂O₅, and K₂O with the main products of field crop rotation crops ranged within 87.2–148.6 kg/ha, 34.3–60.3, and 31.9–57.0 kg/ha, respectively, and was the highest under the application of N110P60K80. Their share was 56–57 %, 22–23 %, and 21–22 %, respectively, depending on the fertilization system, while the ratio of N : P₂O₅ : K₂O was 1 : 0.39–0.41 : 0.36–0.39. The intensity of the balance of the main nutrients depends on their application rates in the crop rotation and varies within a wide range. The application of nitrogen fertilizers at a rate of 110 kg a.i./ha ensured the formation of a nitrogen balance intensity within 93–108 %, which can be considered balanced. The application of phosphorus fertilizers at a rate of 30 kg a.i./ha covered the removal of phosphorus with grain and seed yield by only 52–59 %. A rate of 60 kg a.i./ha, in combination with nitrogen or with nitrogen and potassium, ensured a phosphorus balance intensity of 100–109 %. Potassium fertilizers (40 kg a.i./ha) provided potassium balance intensity at the level of 73–84 %, depending on the experimental variant. This is sufficient for heavy loamy podzolized chernozem with a high potassium content. Conclusions. According to the balance of the main nutrients in the soil, calculated under the condition of their removal from the field only with the main products (grain and seeds), the best experimental variants are N110P60K80 and N110P60K40, as well as N110P60 as a temporary option, considering that heavy loamy podzolized chernozem has significant potassium reserves both in the soil itself and in the parent material.